Modulation of ankle antagonist co-activation during the transition from upright standing to gait and to sit in post-stroke subjects. (1st April 2021) - Ribeiro, Edgar; Silva, Augusta; Pinho, Liliana; Santos, Rubim; Pinho, Francisco; Sousa, Andreia S. P.
Abstract: Introduction: Antagonist co-activation represents a neuronal command for the modulation of muscle synergies with postural control purposes [1 ], probably assuming a key role in the characterisation of tonus dysfunction in post-stroke subjects. This study aims to evaluate the ankle antagonist co-activation during different functional tasks in post-stroke subjects. Materials and methods: A cross-sectional study was performed in eight participants (age = 43.00 ± 10.63 years; median ± interquartile range) who had a subcortical ischaemic stroke in the middle cerebral artery territory for at least 6 months. The study was approved by the local ethics committee and implemented in a research centre. Antagonist co-activation between tibialis anterior (TA) and soleus (SOL) and between TA and gastrocnemius medialis (GM) of the ipsilesional (IPSI) and contralesional (CONTRA) limbs was calculated through electromyographic signals collected during upright standing and postural phases of gait initiation and stand-to-sit, according to the methods proposed by Ribeiro [2 ]. Results: The CONTRA limb presented decreased values in TA/SOL pair during upright standing and increased values in both muscle pairs during gait initiation compared to the IPSI limb (Table 1 ). No significant differences were found between tasks (Table 1 ). Discussion and conclusions: The IPSI and CONTRA limbs presented increased antagonist co-activation when an adequate antigravity function and the coordination of the tibia forward rotation are required, respectively. The comparison of these values with that obtained by healthy subjects [3, 4 ] seems to point to a bilateral postural control dysfunction in post-stroke subjects related to tonus modulation deficits that should be addressed in neurorehabilitation. Future studies with a higher sample are required to extend the results.